2017
DOI: 10.1002/14651858.cd011682.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Self-management interventions including action plans for exacerbations versus usual care in patients with chronic obstructive pulmonary disease

Abstract: Self-management interventions that include a COPD exacerbation action plan are associated with improvements in HRQoL, as measured with the SGRQ, and lower probability of respiratory-related hospital admissions. No excess all-cause mortality risk was observed, but exploratory analysis showed a small, but significantly higher respiratory-related mortality rate for self-management compared to usual care.For future studies, we would like to urge only using action plans together with self-management interventions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
235
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(245 citation statements)
references
References 224 publications
6
235
1
3
Order By: Relevance
“…Although treatment strategies to prevent COPD exacerbations and their subsequent hospital admissions are still largely based on pharmacological therapies, the Global Initiative for Chronic Obstructive Lung Disease 2017 also recommended non-pharmacological treatment, such as self-management interventions with communication with a healthcare professional [2]. The most recent Cochrane review reported that self-management interventions that include written action plans and coaching with a healthcare professional for a prompt treatment of worsening symptoms lead to a lower probability of both respiratory-related and all-cause hospitalisations, and also improve health status [3]. There remain problems with heterogeneity among interventions and consistency in their application that make generalisation difficult in real life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although treatment strategies to prevent COPD exacerbations and their subsequent hospital admissions are still largely based on pharmacological therapies, the Global Initiative for Chronic Obstructive Lung Disease 2017 also recommended non-pharmacological treatment, such as self-management interventions with communication with a healthcare professional [2]. The most recent Cochrane review reported that self-management interventions that include written action plans and coaching with a healthcare professional for a prompt treatment of worsening symptoms lead to a lower probability of both respiratory-related and all-cause hospitalisations, and also improve health status [3]. There remain problems with heterogeneity among interventions and consistency in their application that make generalisation difficult in real life.…”
mentioning
confidence: 99%
“…Instead, we need to use telehealth technologies to our advantage to increase patient activation and empowerment and to facilitate collaboration between patients and healthcare professionals. There is a large volume of evidence that supports self-management programmes in COPD [3,4], but we clearly need a more effective way to implement it. We need to standardise the way symptoms are being monitored and recorded by patients and healthcare professionals.…”
mentioning
confidence: 99%
“…Reasons for readmissions in this chronically ill population are multifactorial and multiple interventions are likely to be required to reduce ED presentations of this critically ill and often frail population. Early clinical follow‐up, nursing outreach visits, self‐management education and timely pulmonary rehabilitation are all likely to play a role …”
mentioning
confidence: 99%
“…1 The review included randomised controlled trials that compared the effectiveness of COPD self-management interventions (that included an action plan for acute exacerbations of COPD) with usual care. Outcomes included health-related quality of life (HRQoL) and respiratory-related hospital admissions.…”
mentioning
confidence: 99%
“…1 The content of the self-management interventions was described as diverse and could include components that were directed towards achieving behaviour change (e.g. smoking, exercise and diet).…”
mentioning
confidence: 99%